Carpentry And Joinery Practice - Brett, Peter, 1950- (Cheltenham : Nelson Thornes, 2004)
Providing complete and up-to-date coverage for NVQ levels 2 and 3, this title has been revised and redesigned to provide an overview of recent changes to NVQ specifications, as well as new construction legislation.
Previous ed.: London: Hutchinson Education, 1981.
Includes index.
Keywords: Carpentry; Joinery; House and Home